(untitled) (Journal of Solar Energy Research Updates, 2022)
Abstract: Several factors affect biogas fermentation, among which the temperature fluctuation is crucial. Domestic and foreign biogas fermentation heating systems are also diverse. Among various exist methods of heating biogas fermentation, solar biogas fermentation heating systems are also diverse. The current study reviewed various solar-heating biogas fermentation systems at home and abroad, describing the principle of the solar-heating system, the collector, the heat storage material and the research and application progress. It briefly discussed its characteristics, summarising the critical technology of solar biogas heating systems.